127k views
1 vote
HELP PLEASEEE. I DONT UNDERSTAND

HELP PLEASEEE. I DONT UNDERSTAND-example-1
User Ewindes
by
5.3k points

1 Answer

5 votes

Answer:

D

Explanation:

So we have the equation:


x^2-6x+58=0

And we want to solve for x.

We can solve it by completing the square.

First, subtract 58 from both sides:


x^2-6x=-58

Divide the b term by 2 and square it:


(-6)/2=-3\\(-3)^2=9

So, add 9 to both sides:


(x^2-6x+9)=-58+9

On the left, the perfect square trinomial pattern. Add on the right. So:


(x-3)^2=-49

Take the square root of both sides:


x-3=\pm √(-49)

The square root of -49 is 7i:


x-3=\pm 7i

Add 3 to both sides:


x=3\pm 7i

So, our answer is D.

And we're done!

User Tomferon
by
5.4k points